Angular Laser Cleaning of Aluminum Al-4004 with Different Spot Sizes - Shaker, Eman; Taha, Ziad Aeyad (Iraqi Journal of Laser, 2023)
Abstract: When it comes to applications in welding, cutting, and surface engineering, the utilization of high-power fiber-delivered beams from solid-state lasers offers several benefits. This paper addresses the issue of cleaning the surface of the samples with different spot sizes (50, 100 and 200) (industrial ytterbium fiber laser) to prepared it to be welded. Angular laser cleaning with incident angles (5, 10, 15, 20, 25, 30) ° with different powers (3, 5, 7, 10) W and hatch distance 0.001 was use for implemented.